REPRESENTATIVE FEMINISM IN CHARLIE’S ANGEL 2019 FILM - Kusumaningtyas, Viola Natasya; Juanda, Juanda (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2022)
The purpose of this study was to determine the values ​​of feminism in the Charlie's Angel 2019 film and to show gender equality. In this study, the researcher used a qualitative method of John Fiske's semiotic analysis. The data sources in this study were obtained from several captures of dialogue and action in the Charlie's Angel film. The object studied is the value of feminism which is taken from several scenes and dialogues in the film. Feminism is an ideology to make people aware of the position of women who are low in society, and the desire to improve or change the situation, Hidayati, (2019). The results of this study indicate that women have a brave, strong attitude, able to do the same things as men, and this film also implies that women can fight against society's negative views on women's abilities. Women are also able to do what men do such as shooting, fighting, leading, and others, so it shows that women are equal to men. Keywords: Feminism, Gender equality, Film